2002
DOI: 10.1038/modpathol.3880485
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Study of Breast Cancer Progression: Different Pathways for Various In Situ Cancers

Abstract: Breast cancer is known to progress through multiple, genomic changes (1-11). These accumulating changes result in the nuclear alterations on which the pathologic diagnosis and microscopic prognosis of cancer are based. The natural history of ductal breast cancer is, even today, only incompletely known. The suggestion that a clonal selection (12) occurs in the progression from atypical hyperplasia toward ductal carcinoma in situ (DCIS) and invasive cancers seems to be supported by recent cytogenetic and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The chromosomal changes seen in atypical hyperplasias are similar to those present in breast cancer [16][17][18], and are consistent with the proposal that AHs are preneoplastic lesions and part of a continuum in the steps toward breast cancer [19,20]. Mariuzzi et al [17] examined the nuclear chromatin pattern in AH and found drastic changes in karyometric features, with these changes similar to those seen in comedo DCIS. Others have noted a high incidence of monoclonality (51.3%) in ADH [21], and an abnormal DNA content [6], consistent with neoplastic transformation.…”
Section: Numerical Chromosomal Changes In Atypical Hyperplasiasupporting
confidence: 76%
“…The chromosomal changes seen in atypical hyperplasias are similar to those present in breast cancer [16][17][18], and are consistent with the proposal that AHs are preneoplastic lesions and part of a continuum in the steps toward breast cancer [19,20]. Mariuzzi et al [17] examined the nuclear chromatin pattern in AH and found drastic changes in karyometric features, with these changes similar to those seen in comedo DCIS. Others have noted a high incidence of monoclonality (51.3%) in ADH [21], and an abnormal DNA content [6], consistent with neoplastic transformation.…”
Section: Numerical Chromosomal Changes In Atypical Hyperplasiasupporting
confidence: 76%
“…Improvements in powerful imaging and data analysis technologies have facilitated the development of quantitative nuclear morphometry as a sensitive tool to identify malignancy associated changes for a variety of cancer types (5,8,13,14,34). Previous studies have demonstrated the potential of automated biosignature feature extraction to classify or monitor neoplastic progression stage using a variety of methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although these observations are consistent with DCIS being a progenitor of IDC, they do not exclude the possibility that DCIS and IDC may have a common progenitor and progress in separate lineages. Observations that have been interpreted specifically as consistent with independent progression of DCIS and IDC have included measurements of nuclear morphometry (Mommers et al, 2001a;Mariuzzi et al, 2002) and microsatellite markers (Fujii et al, 1996;Lichy et al, 2000).…”
Section: Article In Pressmentioning
confidence: 99%